PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN MOTIVASI KERJA GURU TERHADAP KINERJA GURU - M. Ary Irawan; Haromain; Zariani (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
The research aims to determine the influence of the principal's leadership and teacher work motivation on teacher performance. The population in this research are teachers of the data analysis technique used in this research, namely quantitative descriptive. The results of this research show that the principal's leadership significantly influences teacher performance. The research results show that (1) the influence of the principal's leadership on teacher performance is 16.6%, which means that the two variables go hand in hand, the more conducive the principal's leadership is, the better the level of teacher performance. (2) the influence of teacher work motivation on teacher performance is 1.1%, meaning that work motivation can influence teacher performance activities in schools to achieve maximum teacher performance. (3) the influence of principal leadership and teacher work motivation on teacher performance, amounting to 27%, the two variables principal leadership and teacher work motivation go hand in hand with performance, which means that the better the principal's leadership and teacher work motivation, the better the teacher's performance is also high.